Development Of The Weekend Islamic Boarding School Curriculum At The Manbaul Khoir Klodran Islamic Boarding School, Temanggung - Khamim Saifuddin (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2023)
Pesantren Weekend is a collaborative program between formal institutions and Islamic boarding schools. The main goal is to create the next generation of the nation. This research aims to find out how the implementation and development of the curriculum in this weekend pesantren program. The qualitative method with a case study approach was used by the researcher. Research data was taken through direct interview techniques with managers and other stakeholders. To strengthen the data derived from interviews, researchers conducted participant observation directly to the place of activity. As a result, the educational objectives, education system, educational materials, teaching methods, teaching evaluation system still refer to the main principles of the pesantren system. However, the emphasis of this program is on the formation of children's manners towards others. The driving and inhibiting factors for the implementation of the pesantren curriculum come from internal (children, teachers) and external (partner educational institutions, parents and community).